2014
DOI: 10.1016/j.eats.2014.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique for Patch Augmentation of Rotator Cuff Repairs

Abstract: Massive rotator cuff tears defying primary repair have been treated with debridement, arthroscopic subacromial decompression, partial repair, muscle-tendon transfer, and joint prosthesis, among other techniques. However, the treatment results have not been satisfactory compared with those of small-to medium-sized rotator cuff tears; each procedure has its merits and demerits, and currently, there is no single established method. For massive rotator cuff tears defying primary repair, the arthroscopic patch graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
(8 reference statements)
0
4
0
Order By: Relevance
“…One example of this is scaffolds that are designed to augment or bridge the muscletendon-bone unit and eventually incorporate into the host tissue. There are a variety of recent reports of utilizing synthetic scaffolds, biologic scaffolds, treated allograft/xenograft tissue, or autograft tissue to augment rotator cuff repairs [99][100][101][102][103][104][105][106][107]. However, many of these reports consist of technique articles or have short-term follow-up with no control group.…”
Section: Scaffold Augmentationmentioning
confidence: 99%
“…One example of this is scaffolds that are designed to augment or bridge the muscletendon-bone unit and eventually incorporate into the host tissue. There are a variety of recent reports of utilizing synthetic scaffolds, biologic scaffolds, treated allograft/xenograft tissue, or autograft tissue to augment rotator cuff repairs [99][100][101][102][103][104][105][106][107]. However, many of these reports consist of technique articles or have short-term follow-up with no control group.…”
Section: Scaffold Augmentationmentioning
confidence: 99%
“…We did not evaluate the degrees of donor site morbidity. Considering creating donor site morbidity when harvesting Achilles–calcaneus autograft, in the future, an iliotibial band with Gerdy's tubercle [ 27 ] or iliac crest may be a better option in human as the composite autografts or a tissue engineered composite graft. Third, the supraspinatus muscle state was not evaluated before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…69 For these irreparable cases, partial repairs, debridement, biceps tenotomy, tendon transfer and reverse shoulder arthroplasty have been utilized. 10 Bridging patch grafts, using human dermal allograft (HDA) patches, have also been used. Although some authors have reported good outcomes with this technique, others have reported high re-tear rates due to superior translation of the humerus from a lack of restoration of glenohumeral stability.…”
Section: Introductionmentioning
confidence: 99%